Europe enlarged : a handbook of education, labour and welfare regimes in central and eastern Europe / edited by Irena Kogan, Michael Gebel and Clemens Noelke. - Kogan, Irena; Gebel, Michael; Noelke, Clemens (Policy Press, 2008)
This important reference work describes the educational systems, labour markets and welfare production regimes in the ten new Central and Eastern Europe countries.